Analysis of the Protection of Women's Inheritance Rights in the Civil Inheritance Law System - Kumala Dwi Hapsari; Komsatun; Mieke Anggraeni Dewi; Darmawan Tri Budi Utomo (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The protection of women’s inheritance rights represents a fundamental issue within Indonesia’s civil inheritance law system, which continues to encounter various challenges stemming from patriarchal cultural influences and gender-biased social constructs. Although the Indonesian Civil Code (KUHPerdata) explicitly affirms that men and women are entitled to equal rights in inheritance matters, practical realities often reveal persistent disparities in wealth distribution. Such inequities frequently arise from societal perceptions that position men as the principal heirs while viewing women as less entitled to family property. This article aims to examine the legal protection afforded to female heirs within the framework of Indonesia’s civil inheritance law and to evaluate the extent to which principles of equality and non-discrimination have been effectively applied in legal practice. Employing a normative juridical approach, this study analyzes statutory regulations, judicial decisions, and relevant legal literature. The findings indicate that, although civil inheritance law normatively guarantees equal inheritance rights for women and men, gaps remain in its practical implementation. Therefore, strengthening legal protection mechanisms, enhancing gender awareness, and fostering cooperation between law enforcement institutions and women’s advocacy organizations are essential to achieving substantive justice for female heirs in Indonesia.